Daily Smartphone Use for Work and Its Effect on Work-Life Conflict among Integrators - Sheilla Lim, Omar Lim (Faculty of Cognitive Sciences and Human Development, Universiti Malaysia Sarawak (UNIMAS), 2019)
This daily diary study investigates the effects of daily smartphone use for work during off-work hours on work-life conflict. Drawing on role theory which supports the notion that segmentation is a boundary management strategy, the moderating effect of individual’s segmentation preference is proposed. Results of multilevel regression analyses showed that smartphone use for work was positively related to work-life conflict. The result also shows that the preference to integrate work and personal life rather than separate these domains strengthened the relation between smartphone use for work and work-life conflict. The results of this study may help human resource practitioners to better understand the impact of staying connected to work during off-work hours.